1986
DOI: 10.1099/00222615-21-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sero-biotypes of Campylobacter jejuni and C. coli isolated from paediatric patients

Abstract: Summary. During a one-year period, 258 isolates of Campylobacter jejuni and C. coli were obtained from children with gastroenteritis or bacteraemia at the Red Cross Children's Hospital, Cape Town, South Africa. These isolates were biotyped by hippurate hydrolysis, H2S production and tolerance to 2,3,5-triphenyltetrazolium chloride (TTC). Our study indicated that 95.4% of the isolates were C. jejuni biotype 1, 1.5% were,C. jejuni biotype 2 and 3.1% were C. coli; 70% of the isolates were resistant to TTC. Seroty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Isolates from a larger number of patients would be necessary to study this possible relationship in more detail. Among children of the age 0–10 years, Lastovica et al [54]also found differences between HS‐serotypes and age group of the children.…”
Section: Discussionmentioning
confidence: 97%
“…Isolates from a larger number of patients would be necessary to study this possible relationship in more detail. Among children of the age 0–10 years, Lastovica et al [54]also found differences between HS‐serotypes and age group of the children.…”
Section: Discussionmentioning
confidence: 97%
“…The data represent a total of >16,000 strains from developed countries (Penner and Hennessy, 1980; McMyne et al, 1982; Penner et al, 1983; Jones et al, 1985; Patton et al, 1985; Mills et al, 1991; Albert et al, 1992; Skirrow et al, 1993; Marshall et al, 1994; Owen et al, 1994; Nielsen et al, 1997, 2006; Frost et al, 1998; McKay et al, 2001; Oza et al, 2002; Wareing et al, 2002; Woodward and Rodgers, 2002; Karenlampi et al, 2003; Siemer et al, 2004; Cornelius et al, 2005; Fussing et al, 2007; McTavish et al, 2008); and far fewer strains (711) from less developed countries, including Central Africa (Georges-Courbot et al, 1989), South Africa (Lastovica et al, 1986), South Africa (Lastovica et al, 1986), Egypt (Poly et al, 2011), Bangladesh (Neogi and Shahid, 1987), Kuwait (Sjogren et al, 1989), and Thailand (Poly et al, 2011). …”
Section: Cps Typing By Multiplex Pcrmentioning
confidence: 99%
“…In this study, we investigated the rRNA gene restriction patterns (ribopatterns), genomic RAPD-profiles and plasmid profiles of strains of C. jejuni within Penner serotypes 01 and 02, which are two of the most prevalent serotypes in the UK [1] and South Africa [28]. The aim was to determine which method or combination of methods was most discriminatory and reproducible for general typing purposes in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%